Quo Vadis Literacy Education in the Post-Pandemic Era: A Reflection on an Elementary School in Slump Community - Hidayah, Layli; Sueb, Sueb; Sholeh, Muhamad; Widodo, Ganjar S. (International Research-Based Education Journal, 2023)
This study evaluates the school’s policies to implement literacy education at an elementary school during the disruptive moment of global pandemic of covid-19 and social disparity of underprivileged community. Since the global pandemic has hit Indonesia in 2020, it had major impacts on the teaching and learning process across the country, causing some disruption of the educational strategies by the school principals. The purpose of this study is to analyze the policies implemented by the school management in implementing the culture of literacy and numeracy especially during the pandemic. This ethnographic study included one private community-based elementary school in a slump area. The results of this study are that the school had specific policies in order to accommodate the literacy and numeracy practice during the pandemic according to the condition of the community but with least coommunity participation. The policies at the elementary schools dominantly focus on numeracy in the learning process instead of encouraging the literacy practice. The implementation of literacy education at an elementary school in the slump area should have required community participation in order to revitalize its social position to empower the community.